Prenuptial Agreements and Power Relations of Husbands and Wives among Javanese Society - Siti Mas'udah; Shafyra Amalia Fitriany (Jurnal Partisipatoris, 2022)
Javanese still adheres to a patriarchal culture and has the concept of family harmony so that prenuptial agreements are considered as a form of unethical openness that demonstrates a lack of trust in their partners. This study focuses on the meaning of prenuptial agreements and the power relations between husband and wife who enter into prenuptial agreements. This study employed a qualitative research method by conducting in-depth interviews with men and women who made prenuptial agreements. The theory used was phenomenology. This study revealed that prenuptial agreement was defined by various experiences, situations, and personalities of the couple. A prenuptial agreement is not intended to be used to plan a divorce. Pre-nuptial agreement users want a marriage that has protection and freedom. The upper class interprets a prenuptial agreement as a means of protecting property and assets owned, avoiding losses caused by a spouse, and making it easier to run a business. Meanwhile, the middle class interprets prenuptial agreements as a means of self-protection that leads to a guarantee of personal safety over shared assets and other obligations to children fairly in the event of a household conflict. The power relations between husband and wife who enter into prenuptial agreements demonstrate various forms, including: 1) sexist power, 2) female domination, and 3) an equal relationship. This study concludes that Javanese who enters into prenuptial agreements uphold the concept of living in harmony but reject the concept of “surrendering”. Prenuptial agreements are used as: 1) a means of self-protection with security guarantees; the anticipation of the uncertainty of what will happen in the future or the unpredictable in the marriage; and 3) freedom that comes from experience and awareness. Keywords: prenuptial agreement, power relations, marriage, gender equality